Mobile technology generations and cryptographic algorithms: analysis study - Jassim, Khalid Fadhil; Alshaikhli, Imad Fakhri Taha (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Nowadays, Mobile wireless technologies are becoming more significant and growing rapidly for better features and services. Latest Mobile technologies are expected to provide higher processing power, support high quality multimedia applications, offer reliable wireless connections, faster data transmission rates, and consume less power. At the same time, various mobile generations are susceptible to attack via eavesdropping and information leaking operations. Therefore, some cryptographic algorithms have proposed as confidentiality and integrity algorithms in different mobile generations, in order to prevent or mitigate these harmful operations. This paper provides analysis study of Mobile generations (From Mobile 1G to Mobile 4G) and cryptographic algorithms used in these generations. The study based on some factors like features, services, standards, and techniques which have adopted in these generations.